Pendidikan dan Pembinaan Rohani Terhadap Anak TK GKPI Tarutung Kota - Graces Maranata; Dina Rotua Sitanggang; Rogate Wahyuni Lumbantobing; Tri Putri Br. Sinaga; Melina Agustina Sipahutar (JURNAL ILMIAH NUSANTARA, 2024)
Spiritual education in early childhood is an important foundation in shaping their character and morality. Proverbs 6:6-9 provides an important analogy of perseverance and hard work through the example of ants, which can be used as a foundation in educating children to have good habits, discipline, and responsibility from an early age. This article discusses the importance of education and spiritual development for early childhood based on the wisdom found in the book of Proverbs, as well as practical strategies in implementing it in everyday life. Throughout the activity, the PkM team observed that the children were very enthusiastic about the event from start to finish.